2023
DOI: 10.1002/aws2.1318
|View full text |Cite|
|
Sign up to set email alerts
|

The Marshall Fire: Scientific and policy needs for water system disaster response

Abstract: The 2021 Marshall Fire was the costliest fire in Colorado's history and destroyed more than 1,000 homes and businesses. The disaster displaced over 40,000 people and damaged six public drinking water systems. A case study was developed to better understand decisions, resources, expertise, and response limitations during and after the wildfire. The fire caused all water systems to lose power. Power loss was sometimes coupled with structure destruction, distribution depressurization, and the failure of backup po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…By using the author's own supplies, equipment, and conducting chemical analysis in the Indiana laboratory, support from a commercial laboratory was not needed. Though, the impacted well owners and nearby municipalities whose water systems were damaged found great difficulty and 3 to 14 day delays in obtaining supplies to have their water sampled and analyzed (Whelton et al, 2023). It is unclear how impacted households with standing homes would cope with not being able to use their well or plumbing for this time period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By using the author's own supplies, equipment, and conducting chemical analysis in the Indiana laboratory, support from a commercial laboratory was not needed. Though, the impacted well owners and nearby municipalities whose water systems were damaged found great difficulty and 3 to 14 day delays in obtaining supplies to have their water sampled and analyzed (Whelton et al, 2023). It is unclear how impacted households with standing homes would cope with not being able to use their well or plumbing for this time period.…”
Section: Resultsmentioning
confidence: 99%
“…and Town of Superior (13,000 pop. ), where drinking water chemical contamination was found and addressed within several months (Whelton et al, 2023), this unregulated well system still had not restored water pressure to their distribution system 11 months after the fire. Within days after the Marshall Fire, these regulated water systems also obtained technical assistance from the state drinking water agency and out-of-state water system experts.…”
Section: Lessons From An Unregulated Private Multi-home Water Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Since publication of their article, Whelton et al (2023) identified that a figure was referenced where the supplementary materials should have been referenced, and that the supplementary materials did not include important information.…”
mentioning
confidence: 99%